Disruptive democracy the clash between techno-populism and techno-democracy - Bloom, Peter (London SAGE Publications, 2019)
Do new “smart” technologies such as AI, robotics, social media, and automation threaten to disrupt our society? Or does technological innovation hold the potential to transform our democracies and civic societies, creating ones that are more egalitarian and accountable?

Disruptive Democracy explores these questions and examines how technology has the power to reshape our civic participation, our economic and political governance, and our entire existence. In this innovative study, the authors use international examples such as Trump’s America, and Bolsonaro’s recent election as President of Brazil, to lead the discussion on perhaps the most profound political struggle of the 21st century, the coming clash between a progressive “Techno-democracy” and a regressive “Techno-populism”.
Introduction : Democracy Disrupted -- Chapter 1:The Clash of Techno-Politics -- Chapter 2: Outdated Democracy : The Fall of Capitalist Technopoly -- Chapter 3: The Rise of Techno-Populism -- Chapter 4: The Growth of Techno-Democracy -- Chapter 5: The Real Possibilities of Disruptive Democracy -- References -- Index
Keywords: Political participation -- Technological innovations; Political culture; Technology and civilization; Information technology